A Comparative Study of the Reproductive and the Vermicomposting Ability of Three Generations of Epigeic and Anecic Earthworms When Subjected to a Toxic Weed (Ipomoea) as the Sole Feed. Issue 1 (2nd January 2020) - Abbasi, Shahid Abbas; Patnaik, Pratiksha; Abbasi, Tabassum-; Khamrang, Channgam; Abbasi, Tasneem
Abstract: Recent studies by these authors have shown that the toxic and allalopathic weed ipomoea (Ipomoea carnea), gets transformed into benign organic fertilizer when subjected to vermicomposting. To derive benefit from this finding, it is necessary that a process should be made available for uninterrupted and efficient conversion of ipomoea into vermicompost. The present study has been done toward development of such a process, based on the concept of high-rate vermicomposting. It explores the relative ability to vermicompost ipomoea, and to reproduce in ipomoea-fed vermireactors, of successive generations of four species of earthworms — born and raised in ipomoea-fed vermireactors — in comparison to the first generation which had been raised to adulthood on cow-dung. Three epigeic species Eisenia andrei, Peryonix sansibaricus, Lumbricus rubillus, and one anecic Drawida willsi were explored for the purpose. The results, obtained over 480 days of uninterrupted reactor operation, show that the first generation of all four species of earthworms was slow to adapt to the ipomoea feed and took about 40 days to produce consistent quantities of vermicast. The second and the third generations didn't need this adaptation and each generated vermicompost at significantly faster rates than it's previous generation. Overall, the third generation of E. andrei, P. sansibaricus, L. rubellus and D. willsi produced 40, 41, 28, and 26% more vermicast, respectively, than the pioneers of the corresponding species. Similar trend was seen in fecundity as well. Each new generation produced more juveniles and cocoons than the previous generation, the increase being statistically significant at ≥ 95% confidence level. The findings reveal that earthworms can be made to adapt to ipomoea as their sole feed and the earthworm generations born and raised in ipomoea-fed vermireactors display significantly greater vermicomposting ability as well on fecundity than the earthworms which had been cultured on animal manure.